EVALUATION OF OSTEOPATHY IN PATIENTS WITH BETA-THALASSEMIA MAJOR USING DIFFERENT IRON CHELATION THERAPIES - Shawkat, Ali Jalal; Jwaid, Ahmed Hamed; Marzouq Awad, Ghada; Adnan Fawzi, Hayder (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: We aim to assess the bone mineral density (BMD) and bone biochemical parameters in Iraqi patients with Î²-thalassemia major (Î²-TM). Methods: Dual-energy X-ray absorptiometry scan was used to evaluate bone density and interpreted about Z-score which compares to the BMD of age-, sex-, and ethnicity-matched reference population. Biochemical parameters such as calcium, 25-OH Vitamin D, parathyroid hormone, and serum ferritin (SF) evaluated. Results: No statistical difference in SF between pediatrics and adults was determined; however, 66 patients were having their SF between 1000 and 2500 ng/ml and 122 patients with SF Ëƒ2500 ng/ml. Calcium and Vitamin D levels are low in both adults and pediatrics. The bone status shows high percentages of osteoporosis 62% and 54.5% for pediatrics and adults, respectively, as well as osteopenia 27% and 34.3% for both pediatric and adults and to a lesser extent normal bone status 11% for each. Conclusion: Osteopathy has a high prevalence in Iraqi patients with Î²-TM and should receive an optimal transfusion and chelation therapy to prevent bone expansion. Calcium and Vitamin D should be routinely determined to prevent deficiency.